2022
DOI: 10.1128/msphere.00004-22
|View full text |Cite
|
Sign up to set email alerts
|

Glycosuria Alters Uropathogenic Escherichia coli Global Gene Expression and Virulence

Abstract: Uropathogenic Escherichia coli (UPEC) is an important causative agent of urinary tract infections in diabetic humans. We examined the effects of in vitro exposure to glycosuria (presence of glucose in urine) on the virulence and gene expression by UPEC. Our results show that glycosuria rapidly (in 2 h) alters UPEC gene expression, induces biofilm formation, and suppresses type 1 piliation. These results offer novel insights into the pathogenesis of UPEC in the ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
(80 reference statements)
1
3
0
Order By: Relevance
“…The ability of bacteria to respond to this hormone may have a role in the propagation of infection. Previous investigations have shown significantly elevated urinary NE in diabetic patients with and without UTIs [29,30]. In our study we found that NE and glucose both activated the metabolism of the most frequent uropathogens, such as E. coli, Ps.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The ability of bacteria to respond to this hormone may have a role in the propagation of infection. Previous investigations have shown significantly elevated urinary NE in diabetic patients with and without UTIs [29,30]. In our study we found that NE and glucose both activated the metabolism of the most frequent uropathogens, such as E. coli, Ps.…”
Section: Discussionsupporting
confidence: 68%
“…pneumoniae is one of the most common causative organisms of UTIs [28]. Hyperglycemia is frequent in acute patients due to the increased release of stress hormones such as catecholamines and cortisol, but can also result from the cascade effect of proinflammatory cytokines in emergencies such as acute coronary syndrome, pulmonary edema, pulmonary embolism, injuries, severe infections and sepsis [27][28][29][30]. Thus, all these conditions may result in raised levels of NE and glucose in urine and lead to chronic UTIs caused by Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore not surprising that UPEC would rely heavily upon oligo-, dipeptide, and amino acid transporters during UTI ( 15 , 16 ). An exception to this may be during glycosuria in which UPEC shifts toward glycolytic metabolism; however, even in this condition, UPEC was found reliant on the methionine ABC uptake system ( metQN ) ( 57 ). This supports the necessity of ABC importers among a wide variety of infectious niches including rapid growth in planktonic populations, intracellular survival, and diabetic urine.…”
Section: Discussionmentioning
confidence: 99%
“…Research showed that glycosuria exposure augmented group B Streptococcus epithelial adherence and hemolysis and antimicrobial peptide resistance ( John et al., 2021 ). Islam found that glycosuria rapidly increased gene expression encoding biofilm formation and central metabolic virulence of uropathogenic E. coli ( Islam et al., 2022 ). Whether urine glucose plays a greater role in identifying uropathogenic bacteria from colonizers needs more data to be supported.…”
Section: Discussionmentioning
confidence: 99%